Comparative phylogeography shows congruent co-divergence in Neotropical seasonally dry forest and savanna tree species - Vitorino, Luciana Cristina; Reis, Mateus Neri Oliveira; Melo, Warita Alves; Collevatti, Rosane G. [UNESP] (Wiley, 2024)
Aim: The response of South American seasonally dry tropical forest (SDTF) and savanna species to the Quaternary climate changes is still poorly understood. Here we use multi-model inference approach to compare the phylogeography and demographic history of five trumpet tree species (also known as pau-d'arco) and draw general biogeographical patterns: Handroanthus impetiginosus, H. ochraceus, H. serratifolius, Tabebuia aurea and T. roseoalba. Location: Amazonia, Atlantic Forest, Cerrado and Caatinga ecoregions, South America and Brazil. Taxa: Bignoniaceae, Tabebuia Alliance, trees. Methods: We compiled genetic data, occurrence records and ecological niche modelling (ENM) from published articles. We used coalescent modelling to test patterns of co-divergence, and analysed niche breadth and overlap and spatial patterns in genetic diversity using quantile regressions. Results: Species showed concordant lineage divergence times in the Pleistocene. Lineage diversification and phylogeographical patterns are more related to species niche breadth than to biome (savanna or SDTF). Differences in genetic diversity among species matches the expected for the demographic scenarios obtained with coalescent simulations and ENMs: species with wider range expansion during the Last Glacial Maximum had higher diversity than species with range retraction or multiple refugia. Main Conclusions: Diversification burst in the Pliocene, and major diversification of lineages during the Pleistocene seems to be a general pattern in SDTF and savannas in the South America. The high number of haplotypes at the Central Brazil, corresponding to the Cerrado ecoregion, highlights the importance of Protected Areas for SDTFs and savannas, highly threatened biomes in Brazil.
Keywords: Bignoniaceae; dry forest refugia; Neogene; niche overlap; niche similarity; Pleistocene Arc hypothesis; Quaternary climate changes